if m^-1 = -(1/3) then m^-2 equals?

(A) -9

(B) -3

(C) -(1/9)

(D) 1/9

(E) 9

The answer is D and this is how

OG12 explained it

m^-2 is (m^-1)^2 = m^-2. Therefore, we square all of -(1/3) which is = 1/9.

This is how I did it.

m^-1 = 1/m^1 Which in turn is 1/m.

This means that m^-2 = 1/m^2 .

So if 1/m = -(1/3) then 1/m^2 should be -(1/3^2) which is -(1/9). Why do I have to square the entire thing up? I am only squaring the bottom hence why would the negative sign go. Perhaps it's for the 1 and not for the 9?